Uji Aktivitas Antibakteri Ekstrak Metanol Rumput Laut (Kappaphycus alvarezii) pada Berbagai Tingkat Konsentrasi terhadap Pertumbuhan Bakteri Streptococcus mutans - Agus Saifuddin; Sapto Raharjo; Amiruddin Eso (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2015)
Red algae Kappaphycus alvarezii contain flavonoids compound which has activity as an anti bacterial. This study aims to determine the difference of inhibition zone of the growth of Streptococcus mutans bacteria by seaweed methanol extract (K. alvarezii) at each concentrations. This research was conducted by post–test only design (one-shot case study) with a variable treatment of the seaweed methanol extract (K. alvarezii) against S. mutans. Extracts were then divided into 7 concentration of 5%, 25%, 50%, 65%, 75%, 85%, and 95%. Data were analyzed to determine the difference of inhibition zone seen from the ANOVA test (analysis of varience) followed by a post hoc test. The results of the bivariate analysis showed there were no difference of inhibition zone of the growth of S. mutans bacteria by seaweed methanol extract of K. alvarezii at the concentration of 65%, 75%, 85%, and 95% (p = 0,143). This research concluded that there were no defference of inhibition zone of the growth of S. mutans bacteria by seaweed methanol extract of K. alvarezii.Keywords : Kappaphycus alvarezii, Streptococcus mutans